The Implementation of Android-Based Expert System Using Forward Chaining Method for Diagnosing Cat Diseases - Sholihuddin, Ahmad Ahyar; Azizah , Nuril Lutvi; Findawati , Yulian; Mauliana, Metatia Intan (Journal of Technology and System Information, 2024)
The use of mobile devices is increasingly popular due to their user-friendly nature and portability. Expert systems are a component of artificial intelligence that can solve problems typically encountered by experts in determining diagnoses based on specific symptoms. Cats are captivating animals with adorable behaviors, which is why many people choose to have them as pets. As cat owners, it is important for humans to have knowledge about various diseases that can affect cats, as well as preventive measures and treatments to avoid negative impacts on the surrounding environment. The objective of this research is to develop an Android-based expert system application using the forward chaining method to diagnose cat diseases. The development of this system utilizes Android Studio software and employs blackbox testing for evaluation. Based on the research findings, it can be concluded that the implementation of the Android-based expert system application using the forward chaining method functions well, based on the questionnaire completed by 10 cat owners with 5 provided questions. The average result from the user satisfaction questions that have been presented is 88%. The system validation also yielded a result of 80% from 5 tests conducted with users. This application can also help alleviate the workload of veterinarians and cat owners in diagnosing cat diseases, although it cannot replace the role of a veterinarian.